The contribution of PA-X to the virulence of pandemic 2009 H1N1 and highly pathogenic H5N1 avian influenza viruses - Gao, Huijie; Sun, Yipeng; Hu, Jiao; Qi, Lu; Wang, Jinliang; Xiong, Xin; Wang, Yu; He, Qiming; Lin, Yang; Kong, Weili; Seng, Lai-Giea; Sun, Honglei; et al. (Nature Publishing Group, 2015)
PA-X is a novel protein encoded by PA mRNA and is found to decrease the pathogenicity of pandemic 1918 H1N1 virus in mice. However, the importance of PA-X proteins in current epidemiologically important influenza A virus strains is not known. In this study, we report on the pathogenicity and pathological effects of PA-X deficient 2009 pandemic H1N1 (pH1N1) and highly pathogenic avian influenza H5N1 viruses. We found that loss of PA-X expression in pH1N1 and H5N1 viruses increased viral replication and apoptosis in A549 cells and increased virulence and host inflammatory response in mice. In addition, PA-X deficient pH1N1 and H5N1 viruses up-regulated PA mRNA and protein synthesis and increased viral polymerase activity. Loss of PA-X was also accompanied by accelerated nuclear accumulation of PA protein and reduced suppression of PA on non-viral protein expression. Our study highlights the effects of PA-X on the moderation of viral pathogenesis and pathogenicity.